Pengaruh Faktor Sosio Budaya Terhadap Aras Kesuburan Wanita Melayu Di Mukim Chetok, Jajahan Pasir Mas, Kelantan - Nor, Nik Norliati Fitri Md (2010)

(untitled)
This research base on fertility level among Malay woman that conducted in Mukim Chetok, District of Pasir Mas, Kelantan involving studies in socio culture. This research use questionnaire form to interview sample size of 318 married women respondent chosen using Random number table method. The study show min age of respondent was 44.04 year and 37.1 percent respondent educated at level SPM, 30.5 percent primary school level and below, PMR level was 27.7 percent. As much as 87.1 percent respondents are not working and have income below poverty line. This study also show that min age for respondent to first marriage was below 20.9 year. Malay women’s fertility level in research area was high and the average number of child of respondent was 5.8 children per women.